2018
DOI: 10.1002/bdr2.1424
|View full text |Cite
|
Sign up to set email alerts
|

Aerodigestive and communicative behaviors in anencephalic and hydranencephalic infants

Abstract: The aerodigestive and communicative behaviors of anencephalic and hydranencephalic patients are assessed from literature sources and are compared with documented neural structures present in the brainstem, subcortical, and cortical regions of the brain. Much of the data analyzed corroborate previous neurological studies, which focus on central pattern generators and development in model organisms. However, findings suggest that further research is necessary to determine which components of these systems suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…One method for testing this hypothesis may be to investigate the facial mimicry ability of anencephalic patients. It has been reported that anencephalic infants, who generally develop neither the neocortex, limbic regions, nor cerebellum (Radford et al, 2019 ), show spontaneous facial expressions such as smiling and crying (Dickman et al, 2016 ; Melnick et al, 1987 ; Shewmon et al, 1999 ); this suggests that their facial nerve nucleus can catalyze the production of facial expressions. If these patients are capable of facial mimicry, the facial nerve nucleus would be the primary candidate responsible for matching between the observation/execution of facial expressions.…”
Section: Discussionmentioning
confidence: 99%
“…One method for testing this hypothesis may be to investigate the facial mimicry ability of anencephalic patients. It has been reported that anencephalic infants, who generally develop neither the neocortex, limbic regions, nor cerebellum (Radford et al, 2019 ), show spontaneous facial expressions such as smiling and crying (Dickman et al, 2016 ; Melnick et al, 1987 ; Shewmon et al, 1999 ); this suggests that their facial nerve nucleus can catalyze the production of facial expressions. If these patients are capable of facial mimicry, the facial nerve nucleus would be the primary candidate responsible for matching between the observation/execution of facial expressions.…”
Section: Discussionmentioning
confidence: 99%